Differences in pregnancy outcomes, prenatal care utilization, and maternal complications between teenagers and adult women in Korea: A nationwide epidemiological study. Issue 34 (August 2016) - Lee, Sang Hyung; Lee, Seung Mi; Lim, Nam Gu; Kim, Hyun Joo; Bae, Sung-Hee; Ock, Minsu; Kim, Un-Na; Lee, Jin Yong; Jo, Min-Woo
Abstract : Abstract: Teenage mothers are at high risk for maternal and neonatal complications. This study aimed to evaluate the socioeconomic circumstances of teenage pregnancy, and determine whether these increased risks remained after adjustment for socioeconomic circumstances in Korea. Using the National Health Insurance Corporation database, we selected women who terminated pregnancy, by delivery or abortion, from January 1, 2010 to December 31, 2010. Abortion, delivery type, and maternal complications were defined based on the International Classification of Diseases-10th Revision. We compared teenagers (13–19 years at the time of pregnancy termination) with other age groups and investigated differences based on socioeconomic status, reflected by Medical Aid (MA) and National Health Insurance (NHI) beneficiaries. We used multivariate analysis to define the factors associated with preterm delivery. Among 463, 847 pregnancies, 2267 (0.49%) involved teenagers. Teenage mothers were more likely to have an abortion (33.4%) than deliver a baby when compared with other age groups (20.8%; P  < 0.001). About 14.4% of teenage mothers had never received prenatal care throughout pregnancy. Among teenage mothers, 61.7% of MA recipients made fewer than 4 prenatal care visits (vs 38.8% of NHI beneficiaries) ( P  < 0.001). Teenage mothers more often experienced preterm delivery and perineal laceration ( P  < 0.001). Teenage mothers (<20 years) were 2.47 times more likely to have preterm delivery than older mothers (20–34 years; P  < 0.001). Teenage mothers had higher risk of inadequate prenatal care and subsequently of preterm delivery, which remained significantly higher after adjusting for socioeconomic confounding variables and adequacy of prenatal care in Korean teenagers ( P  < 0.001).